Examining the association of neighborhood conditions on attention‐deficit/hyperactivity disorder symptoms in autistic youth using the child opportunity index 2.0 - Catrina A. Calub; Irva Hertz‐Picciotto; Deborah Bennett; Julie B. Schweitzer (JCPP Advances)
Abstract Background While neighborhood conditions have previously been shown to have substantial effects on later occupational, educational and health outcomes, this is the first study to examine the relation between neighborhood factors and attention‐deficit/hyperactivity disorder (ADHD) symptoms in children with autism and developmental delays. Methods Children from the CHARGE (Childhood Autism Risks from Genetics and the Environment) Study were evaluated at ages 2–5 years and then later in the ReCHARGE (follow‐up) Study at ages 8–20 years (mid‐childhood/adolescence). Using linear regression, we assessed associations between the Child Opportunity Index 2.0 (COI) at birth, a multidimensional neighborhood measure of childhood opportunity, and ADHD symptoms on the Aberrant Behavior Checklist at mid‐childhood/adolescence. Results Participants included a total of 524 youth (401 males; 123 females), composed of 246 autistic children (AUT), 85 children with Developmental Delays (DD) without autism, and 193 Typically Developing (TD) children. Mean age was 3.8 years (SD = 0.79) when evaluated at CHARGE and 13.5 years (SD = 3.69) when evaluated at ReCHARGE. Regression analyses revealed COI at birth significantly predicted ADHD symptoms during mid‐childhood/adolescence and early childhood diagnosis modified the COI effect. More specifically, COI significantly predicted ADHD symptoms in the AUT group, but not the TD or DD groups. Additional regression analyses indicated that this interaction was only present in the Social and Economic COI domain. Secondary analyses revealed autistic youth with High and Low Social and Economic COI domain scores had similar levels of ADHD symptoms during early childhood, but by mid‐childhood/adolescence, those with low Social and Economic COI domain scores had higher ADHD symptoms. Conclusions Among autistic, but not TD or DD youth, poorer neighborhood conditions at birth predict greater ADHD symptoms in later development. These findings have important clinical implications and highlight the need for increased and improved resources in poorer neighborhoods to reduce existing disparities in ADHD, a common neurodevelopmental impairment.